2017
DOI: 10.1021/acs.macromol.6b02702
|View full text |Cite
|
Sign up to set email alerts
|

Buta-1,3-diyne-Based π-Conjugated Polymers for Organic Transistors and Solar Cells

Abstract: We report the synthesis and characterization of new alkyl-substituted 1,4-di­(thiophen-2-yl)­buta-1,3-diyne (R-DTB) donor building blocks, based on the −CC–CC– conjugative pathway, and their incorporation with thienyl-diketopyrrolo­pyrrole (R′-TDPP) acceptor units into π-conjugated PTDPP-DTB polymers (P1–P4). The solubility of the new polymers strongly depends on the DTB and DPP solubilizing (R and R′, respectively) substituents. Thus, solution processable and high molecular weight PDPP-DTB polymers are achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…These physical quantities not only provide extended π‐electron delocalization to facilitate charge transport, but were also found to control the overall morphological ordering and crystallinity of the thin films. Additional studies have analyzed the size of the crystalline domains and related them to a trade‐off relationship with the ability to transport charge and recombination reactions of the charge carriers . The results presented in this paper are relevant to the above discussion and should be attractive to the broad field of fundamental studies of organic semiconducting materials and applications.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…These physical quantities not only provide extended π‐electron delocalization to facilitate charge transport, but were also found to control the overall morphological ordering and crystallinity of the thin films. Additional studies have analyzed the size of the crystalline domains and related them to a trade‐off relationship with the ability to transport charge and recombination reactions of the charge carriers . The results presented in this paper are relevant to the above discussion and should be attractive to the broad field of fundamental studies of organic semiconducting materials and applications.…”
mentioning
confidence: 88%
“…These self‐assembled aggregates have paved the way for a groundbreaking opportunity to control intra‐ and interchain order, which is necessary to overcome polydispersity effects and increase structural ordering and crystallinity . The ability to control these morphological variables has important consequences for the macroscopic physical properties of these materials and are thus paramount to the development of technological applications . Although strategies to produce ordered aggregate formation of P3HT that self‐assemble in solution have been vastly documented, including solvent mixture, solution aging, temperature, chemical doping, high‐energy and ultrasound treatments, they have often shown limited efficiencies of aggregate generation and/or poor quality of the crystalline domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Baker's yeast was used as biocatalyst to reduce a,b-unsatu- Organic semiconducting materials based on 1,3-butadiyne unit were reported for the rst time in 2017 by Brian J. Eckstein and co-workers. 249 Alkyl-substituted 1,4-di(thiophen-2-yl)buta-1,3-diyne (R-DTB) donor building blocks were polymerized with thienyldiketopyrrolopyrrole (R 0 -TDPP) acceptor units to afford p-conjugated polymers TDPP-DTB, in which R and R 0 groups were varied to obtain four different polymers (199)(200)(201)(202). The solubility of the newly synthesized polymers was revealed to be strongly dependent upon the substitution pattern of the DTP In 2017, Wenbin Lai and co-workers reported the synthesis of three novel single-component conjugated polymers possessing diketopyrrolopyrrole (DPP)-based backbone and perylene bisimide (PBI) as pendant connected with exible alkyl chains for single-component organic solar cells (SCOSCs).…”
Section: Pd-catalyzed Stille-coupling Polymerizationmentioning
confidence: 99%
“…13,14 Recently, organic semiconductors such as polymers and small organic molecules nd tremendous applications towards optoelectronic devices. 26,27 In organic semiconductor devices, the metal oxide semiconductors such as TiO 2 , ZnO and SnO 2 were replaced by exible organic semiconducting materials having high electrical conductivity (higher than that of metal oxide semiconductors), [28][29][30] Furthermore, the optoelectronic properties of the organic semiconductors were improved by functionalization or by making composite with GO/rGO. Zheng et al 14 reported that the photo generated charge carrier transport kinetics in organic semiconductor, poly(3-hexylthiophene) has been signicantly improved when GO and rGO (acceptor) was added.…”
Section: Introductionmentioning
confidence: 99%